John Stuart Mill’s Idea of History: A Rhetoric of Progress - López, Rosario (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
This paper examines the crucial role the idea of history plays in John Stuart Mill’s social and political thought. Insofar as Mill argues that historical change and progress are synonyms, the latter deserves a careful attention. However, academic literature has mostly regarded Mill’s philosophy of history a topic of minor importance. Some of his philosophical views on history, it will be argued, clearly affect his political views, but they also inform his scientific study of society. Accordingly, historical research aims both at understanding the past to guide society’s future. By analysing the different sources from which Mill draws inspiration, the paper considers his views against the background of his personal and intellectual context. Mill’s temporary depression, along with Macaulay’s criticism of the utilitarian ahistorical conception of politics, triggers an enquiry into the appropriate method to study society, which eventually places history at its core. His reading of Coleridge and a number of French thinkers reflects a renewed interest in the discipline. The article discusses, first, Mill’s interpretation of Coleridge as Bentham’s opposite pole. Later in the article, I highlight Mill’s debts to Comte and Saint- Simon, especially as regards what he calls the “Inverse Deductive Method”. Some remarks on French historiographers, like Mignet, Dulaure, Sismondi, Michelet and Guizot, also support my argument.